How do different innovation forms mediate the relationship between environmental regulation and performance? - Hu, D; Wang, Y; Huang, J; Huang, H (Elsevier, 2017)
The Porter Hypothesis (PH) challenges the traditional view on the relationship between environmental regulation and performance by arguing that different innovation forms stimulated by regulations can improve firm performance. However, little of the extant literature discusses how different innovation forms mediate the relationship involved in the Porter Hypothesis. Therefore, in this study, we attempt to provide a model to compare the mediation roles of process innovation and product innovation in the PH, using data from 35 industrial sectors in China from 2001 to 2010. Empirical results indicate that while both process innovation and product innovation mediate the causal link between environmental regulation and performance, product innovation has a slightly stronger mediation effect than process innovation.